Estuary and Marine Waters Characteristics of the Sungai Nibung Village Coastal Waters, Kubu Raya, West Kalimantan - Mega Sari Juane Sofiana; Ikha Safitri; Arie Antasari Kushadiwijayanto; Yusuf Arief Nurrahman; Harianto Harianto (Jurnal Ilmu Pertanian Indonesia, 2026)
Sungai Nibung Village is a KKPP3K (Coastal Waters and Small Islands Conservation Area) in Kubu Raya District. This community features an abundance of diverse natural resources, such as crab, fish, shrimp, squid, octopus, and finless dolphins. This indigenous biota is sustained by fertility and high water quality. Water fertility reveals high nutrient concentration and identifies phytoplankton as primary producers. Water contains nutrients in the form of nitrates and phosphates. Phytoplankton and other aquatic species require these nutrients to survive. The concentration of chlorophyll-a, the primary pigment of phytoplankton, which has a role in photosynthesis, can also be used to estimate the trophic state of waterways. The fertility of Sungai Nibung Village waters in the sea (Station I and II), estuary (Station III), and river (Station IV and V) has been assessed. Nitrate and phosphate levels in water samples were assessed in line with SNI 06-2480-1991 and SNI 06-6989.31.2005, respectively. The chlorophyll-a was evaluated using the trichromatic method with a UV-Vis spectrophotometer at 664, 647, and 630 nm. Sungai Nibung Village's waters include 0.9−1.5 mg/L nitrate and 2.06−2.19 mg/L phosphate. Chlorophyll-a levels range from 2−5 μg/L, placing them in the low category. Keywords: chlorophyl-a, Sungai Nibung Village, nitrate, phosphate